Analisis Capaian Kinerja Dengan Model Regresi Linear Pada Perancangan Sistem Informasi Capaian Kinerja Dirjen Migas - Akil, Ibnu (CV. Hawari, 2024)
To monitor the performance of the government or government unit, a performance report is required. When submitting reports, you should utilize information technology. The Director General of Oil and Gas still uses the Excel application in reporting, this reduces one of the performance assessment points. In determining the performance percentage, a special formulation is required. The aim of this research is how to transform the Excel application into a web-based information system using a linear regression model in calculating performance achievements. From the results of testing and implementation of the linear regression model, we succeeded in calculating the performance percentage according to the Excel results.